Faktor Yang Mempengaruhi Financial Distress Pada Perusahaan Manufaktur Yang Terdaftar Di BEI - Jessica Lienanda, Agustine Ekadjaja (Jurnal Paradigma Akuntansi, 2019)
The purpose of this research is to examine empirically the influence of Liquidity, Leverage, and Firm Size to Financial Distress. Population of this study is manufacturing companies listed on Indonesia Stock Exchange during 2015-2017 periods which using audited annual report. Sample selection technique used in this research is by purposive sampling method. There are 12 companies are selected as sample and processed by using SPSS software version 21. This research used logistic regression analysis. Based on the result of analysis concluded that liquidity has negative and significant influence to financial distress. Leverage has positive and significant influence to financial distress. Firm size has insignificant influence to financial distress